Stereocontrolled spirocyclic bislactams derived from pyroglutamic acid - Hill, T; Kocis, P; Moloney, M (2006)
The synthesis of rigid spirocyclic bislactams derived from pyroglutamic acid has been established. © 2005 Elsevier Ltd. All rights reserved.